2015
DOI: 10.1590/1807-3107bor-2015.vol29.0098
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social determinants on schoolchildren’s oral health in Brazil

Abstract: The aim of this study was to evaluate the impact of socioeconomic status, home environment, and self-perception of health conditions on schoolchildren's dental caries experience. A total of 515 twelve-year-old schoolchildren from Juiz de Fora, State of Minas Gerais, Brazil, were selected into a random multistage sample. The schoolchildren were examined for the presence of caries lesions using the decayed/missing/filled teeth (DMFT) index and categorized as caries-free (DMFT = 0) or with caries experience (DMFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 18 publications
3
22
1
5
Order By: Relevance
“…The caries prevalence varies around the world. Hence, other than the similar results 25 , there are lower 26 or higher 27 caries incidences than this study. Our results were lower than the previous Turkish studies.…”
Section: Discussionsupporting
confidence: 52%
“…The caries prevalence varies around the world. Hence, other than the similar results 25 , there are lower 26 or higher 27 caries incidences than this study. Our results were lower than the previous Turkish studies.…”
Section: Discussionsupporting
confidence: 52%
“…Individuals belonging to higher income groups are less likely to report dental pain and more likely to be satisfied with their oral health status than their lower socioeconomic counterparts (5). It was also observed that socioeconomic factors are considered to be a strong risk factor for school children caries (7). One study on the trends in tooth loss in Swedish women observed that women in lower social groups tended to have less remaining teeth, irrespective of age (8).…”
Section: Introductionmentioning
confidence: 99%
“…Type of school is also a significant determinant of caries experience in Brazil. 31 School-based intervention focusing on tooth brushing and other preventive measures, however, may not be effective in preventing caries 32 except in certain controlled trials, such as dental sealant programs. 33 This study also found that girls and students at older ages were at higher risk for developing caries, which might indicate dietary habits and direct biological effects as factors contributing to caries experiences.…”
Section: Discussionmentioning
confidence: 99%